Training to Improve the Knowledge, Attitude, and Motivation of Communities to Conserve Groundwater in the South Coastal Region of Gorontalo - Aryati Alitu; Bakhrani A. Rauf; Ichsan Ali (International Journal of Education, Vocational and Social Science, 2024)
Groundwater conservation training is a strategic effort to increase the capacity of coastal communities in dealing with the threat of clean water shortages due to environmental degradation. This study aims to determine: (1) groundwater conservation knowledge, attitude to maintain groundwater sustainability, and motivation to conserve natural water resources available in the coastal area of Gorontalo South Coast, (2) effectiveness of groundwater conservation training to improve knowledge, attitude, and motivation of the community in the coastal area of Gorontalo South Coast. This research is an experimental research located in the coastal area of North Leato Village. The sample was 25 people, selected by purposive sampling method. The variables considered were: (1) knowledge of groundwater conservation, (2) attitude towards preserving groundwater, (3) motivation to conserve groundwater resources, (4) effectiveness of training on increasing knowledge, attitude and motivation of the community to conserve groundwater. The experimental design used was One Group Pretest-Postes Design. The data analysis used was descriptive statistical analysis and inferential statistical analysis. The inferential model used was dependent t test. The results showed: (1) knowledge of groundwater conservation, attitudes to maintain groundwater sustainability, and motivation to conserve groundwater resources before training are in the low category, after training are in the high category, (2) training has a very significant effect on increasing knowledge, attitudes and motivation of the community to conserve groundwater in the coastal area of North Leato Village.